Expanding the landscape: developing knowledgeability through communities of practice. Issue 3 (3rd July 2018) - Brown, Melanie; Peck, Catherine
ABSTRACT: Rapid changes in the Higher Education (HE) sector are increasing the pressure on teaching staff to introduce technology-enhanced learning experiences into the curriculum. Institutions therefore need to provide effective means of enabling academics to successfully transition to these new modes of curriculum delivery. This paper reports on an inquiry into the efficacy of a community of practice (CoP) approach trialled at a HE institution to contribute to the design of a renewed, blended curriculum. Analysis indicated that participation in the CoP had a positive impact on academics' sense of community and their knowledgeability in relation to new teaching approaches.